2021
DOI: 10.3389/fnagi.2020.584244
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Retinal Nerve Fiber Layer Thickness and Clinical Symptoms of Alzheimer's Disease

Abstract: Background/Aim: Retinal nerve fiber layer (RNFL) thickness (RT), which can reflect the status of the retinal optic nerve cells, may be affected in patients with Alzheimer's disease (AD). There are few studies on the correlation of RT of patients with AD (AD-RT) with clinical symptoms of various cognitive domains, neuropsychiatric symptoms, and activities of daily living (ADL). This study is to investigate the relationships between RT and the abovementioned clinical symptoms of AD.Methods: A total of 96 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(55 reference statements)
2
3
0
Order By: Relevance
“…45,46 When attenuation of the RNFL was found in Alzheimer disease, it was noted primarily in the superior and inferior quadrants. [47][48][49] Similarly, when analyzing the quadrant data of our cohort, we found thinning of the inferior quadrant in the DLB group. The decreased GC-IPL thickness in our study mirrors findings in previous studies of DLB and prodromal Lewy body dementia.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…45,46 When attenuation of the RNFL was found in Alzheimer disease, it was noted primarily in the superior and inferior quadrants. [47][48][49] Similarly, when analyzing the quadrant data of our cohort, we found thinning of the inferior quadrant in the DLB group. The decreased GC-IPL thickness in our study mirrors findings in previous studies of DLB and prodromal Lewy body dementia.…”
Section: Discussionsupporting
confidence: 68%
“…45,46 When attenuation of the RNFL was found in Alzheimer disease, it was noted primarily in the superior and inferior quadrants. 47 49 Similarly, when analyzing the quadrant data of our cohort, we found thinning of the inferior quadrant in the DLB group.…”
Section: Discussionsupporting
confidence: 61%
“…After that, other relevant studies appeared successively to confirm this discovery (Bayhan et al, 2015;Bulut et al, 2016;Cunha et al, 2017b). Lian et al (2020) performed a comparative experiment between AD patients with abnormal and normal retinas. 96 AD patients were divided into 52 (54.17%) AD patients with an abnormal RNFL thickness and 44 (45.83%) AD patients with a normal RNFL thickness.…”
Section: Conventional Optical Coherence Tomography In Admentioning
confidence: 88%
“… Lian et al (2020) performed a comparative experiment between AD patients with abnormal and normal retinas. 96 AD patients were divided into 52 (54.17%) AD patients with an abnormal RNFL thickness and 44 (45.83%) AD patients with a normal RNFL thickness.…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 99%
“…For example, retinal thickness measurements based on OCT have been used to diagnose and monitor multiple sclerosis (MS) [22][23][24]. Other studies have demonstrated an association between a thinner retinal nerve fiber layer (RNFL) and the diagnosis of Alzheimer's disease (AD) [25][26][27][28][29], which accounts for more than 60% of clinical dementia. A major area of OCT-based oculomics is the early detection of pre-clinical NDDs.…”
Section: Introductionmentioning
confidence: 99%